An update on prucalopride in the treatment of chronic constipation. (November 2017) - Omer, Anam; Quigley, Eamonn M.M.
Chronic constipation (CC) is a highly prevalent and often under-appreciated gastrointestinal disorder associated with significant impairment in quality of life. Symptoms of constipation are typically present for a number of years prior to a patient seeking help. Lifestyle modifications followed by, or coupled with, over-the-counter laxatives represent the initial treatment option; however, relief for many is limited and dissatisfaction rates for these approaches remain high. Over recent years, therefore, considerable effort has been exerted on the development of novel pharmacological approaches. Two major targets have emerged, motility and secretion. Research on the former led to the development of a number of prokinetic agents capable of stimulating colonic motility and, thus, accelerating colonic transit. Of these, earlier prototypes such as cisapride and tegaserod, though effective, were ultimately withdrawn due to cardiovascular adverse events due in part to receptor non-selectivity. Highly selective serotonergic receptor agonists have since emerged which appear to be equally effective in stimulating gut motility but are devoid of cardiac side effects. One such agent is prucalopride, which has now been approved for the management of chronic idiopathic constipation in several countries, but not in the United States. Multiple multicenter, randomized placebo-controlled clinical trials have demonstrated superiority for prucalopride compared to placebo in the short to medium term in relieving the major symptoms of constipation in both men and women across a broad spectrum of ages, ethnicities and geographic locations. To date, prucalopride has enjoyed a favorable safety profile and there have been no signals to suggest arrythmogenicity. Efficacy over longer periods of treatment remains to be confirmed. Evidence for efficacy in other forms of constipation, such as opioid-induced constipation and that related to Parkinson's disease is beginning to emerge; its status in the management of constipation-predominant irritable bowel syndrome or foregut motility disorders, such as gastroparesis, remains to be established.